Sobre los límites del campo : Ensayos de crítica literaria latinoamericanista - Beverley, John, 1943- (Book collections on Project MUSE., 2022)
"A collection of selected essays by critic John Beverley in the field of literary Latin Americanism, attentive to the connections between literature, hegemony, and social conflict. It covers the period from the eighties of the last century to today. Topics include the colonial baroque and its hegemonic force in Latin American culture, testimony as an emerging genre, militant literature, postmodernism, the relationship between literary and cultural criticism and the development of the so-called Pink Tide, and in general the impact of postcolonial and subaltern studies. The collection provides a critical vision of the Latin American literate city and a defense of the field of literary criticism as a place to constitute and reconstitute hegemony. In this sense, it stands both against the so-called 'crisis in the humanities' induced by the ideological effects of neoliberalism, but also against critical positions, such as deconstruction, which aspire to a transcendence of literary criticism as such, and of the project of Latin Americanism in general terms"--